Pendampingan Manajerial Santri Melalui Pelatihan Leadhershep di Asrama Al-Maliki Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan - Muhammad Haris; Fahrur Rosikh; Ahmad Ainun Na’im; Ahmad Muadhim (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
His mentoring intends to develop the assets of the al Maliki dormitory community at the Sunan Drajat Islamic Boarding School Lamongan to apply managerial assistance to Al Maliki students in this mentoring leadhershep training using the ABCD method. Based on the results of the mentoring of the Asset Based Community Development (ABCD) method, it can be concluded that mentoring in the managerial assistance of al Maliki santri in leadhershep training will not succeed if there is no cooperation and active participation from the subject of mentoring, dormitories, foundations, especially institutions. In this era of reform and the spirit of decentralization, Islamic boarding schools need to be managed more proactively for the future of santri as quality human resources and have good morals. To achieve this goal, competencies are needed as professional human resources.